Performances analysis of Sugar/EPR, Lithium Formate Monohydrate/EPR and Sulfamic acid/EPR dosimetry systems in evaluation of doses delivered during the prostate cancer treatment, using an anthropomorphic phantom - Fatna ZAHIRI; Mohammed MIKOU; Redouane EL BAYDAOUI; Kamal Saidi; Hanae EL GOUACH (Iranian Journal of Medical Physics)
Introduction: The aim of this work is to test the suitability of the three dosimetry systems: sugar/EPR (Electron Paramagnetic Resonance), lithium formate monohydrate/EPR (LFM/EPR) and sulfamic acid/EPR in the control and assessment of the dose delivered in tumor volume and surrounding organs during radiotherapy treatment of prostate cancer. Thus, the study proposes to compare the doses calculated by the treatment planning system (TPS) with the doses measured by the three dosimetry systems used, in order to verify their ability to evaluate the clinical doses administered. Material and Methods: To perform this work, the various dosimeters studied were placed at the level of the tumor and the surrounding organs in a male anthropomorphic phantom. To simulate radiation therapy for prostate cancer, the phantom used was irradiated by 6 MV X-rays after careful implementation of a treatment plan for the determination and execution of the prescribed dose, using CT (Computed Tomography) imaging and TPS calculations. Results: The irradiated dosimeters were analyzed by EPR and the determined doses were compared to the doses calculated by the TPS system. The results obtained show that the doses measured by the studied dosimetry systems are similar to calculated doses. The sugar/EPR system appears to be more accurate than the other two dosimetry systems. Conclusion: The three dosimetry systems used show promise for applications as dosimeters in radiotherapy.